Втрачені образи українського світу (з робочого столу лексикографа) .......... 581 - Карпіловська, Євгенія А. (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
LOST IMAGES OF THE UKRAINIAN WORLD (FROM A LEXICOGRAPHER’S WORKSHOP) The article is devoted to the problem of nationally-marked Ukrainian vocabulary and phraseology, and their role in the formation of the national consciousness and national identity of the Ukrainians. By comparing Ukrainian dictionaries from the second half of the 19th and early 20th centuries, with dictionaries of the Soviet period, the paper reveals the results of the forced rapprochement of the Ukrainian language to Russian. It highlights deformations such as the removal of proper names, and replacing them with calques from Russian; and also the imposition of Russian meanings onto Ukrainian words in the cases of cross-linguistic homonyms. The article emphasises the need for a critical analysis of the modern Ukrainian vocabulary, and the development of criteria for the restoration of words and idioms that are important for the Ukrainian linguistic image of the world as symbols of the Ukrainian ethnoculture.